Foreign Language Learning Motivation in Higher Education: A Longitudinal Study of Motivational Changes and Their Causes. Issue 2 (24th May 2013) - Busse, Vera; Walter, Catherine
ABSTRACT This article reports on a study involving first‐year modern foreign languages students enrolled in German degree courses at two major universities in the United Kingdom. It explores the experience of these students from a motivational angle. A longitudinal mixed‐methods approach was employed in order to address the time‐ and context‐sensitive nature of motivational attributes. The data suggest that despite students' increasing wish to become proficient in German, their effort to engage with language learning decreased over the course of the year. This change occurred in conjunction with decreasing levels of intrinsic motivation and self‐efficacy beliefs. The relationships between motivational changes and contextual factors in higher education are discussed against the backdrop of students' transition experience from school to university. The article concludes by outlining pedagogical suggestions for how to counteract decreasing motivation of modern foreign languages students during their first year university studies.